2021
DOI: 10.3390/foods10010117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Steaming and Fermentation on Nutritive Values, Antioxidant Activities, and Inhibitory Properties of Tea Leaves

Abstract: Fermented tea (Cha-miang in Thai) is a local product made by traditional food preservation processes in Northern Thailand that involve steaming fresh tea leaves followed by fermenting in the dark. Information on changes in nutritive values, bioactive compounds, antioxidant activities, and health properties that occur during the steaming and fermenting processes of tea leaves is, however, limited. Changes in nutritive values, phenolics, antioxidant activities, and in vitro health properties through inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 61 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…They demonstrated that quercetin (which is an important phenolic component of tea) can react with a magnesium cation (Mg +2 ) through the chelation site in the quercetin molecule, which increases its antioxidant activity. Many authors proved that polyphenols are the most important antioxidant components found in tea leaves [3,5,6,10,19]. Samadi & Fard [29] indicated that a particular antioxidant effect in tea infusions was exhibited by tannins and flavonoids, for which the correlation coefficient values specifying their relationships with antioxidant activity were statistically significant and amounted to r = 0.721 and r = 0.740, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that quercetin (which is an important phenolic component of tea) can react with a magnesium cation (Mg +2 ) through the chelation site in the quercetin molecule, which increases its antioxidant activity. Many authors proved that polyphenols are the most important antioxidant components found in tea leaves [3,5,6,10,19]. Samadi & Fard [29] indicated that a particular antioxidant effect in tea infusions was exhibited by tannins and flavonoids, for which the correlation coefficient values specifying their relationships with antioxidant activity were statistically significant and amounted to r = 0.721 and r = 0.740, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The most common classification of teas involves their division according to the leaf fermenting method. A distinction is made here between the almost unfermented white, yellow, and green teas, partially fermented oolong and pu-erh, and the fully fermented black tea [5]. Due to the sensory characteristics, the most popular is black tea, although interest in green tea has also been on the increase for many years [6].…”
Section: Introductionmentioning
confidence: 99%
“…The lipase inhibitory activity was determined using Candida rugosa lipase (tуре VII, 700 unit/mg, 100 μL of 0.01 mg/mL) as an enzyme, 5-5ʹ-dithiobis(2-nitrobenzoic-Nphenacyl-4,5-dimethyуhiаzolium bromide) (50 μL of 0.2 mM) as a substrate, 5,5′-dithiobis(2-nitrobenzoic acid) (DTNB, 10 μL of 16 mM) as an indicator, and a plant extract (40 μL) as an inhibitor as previously described [56]. The inhibitory activity was monitored at 412 nm using the microplate reader, and the results were expressed as the inhibition percentage using the following equation…”
Section: Enzyme Inhibitory Activitiesmentioning
confidence: 99%
“…where A is the initial velocity of the control reaction with an enzyme (control), a is the initial velocity of the control reaction without enzyme (control blank), B is the initial velocity of the enzyme reaction with extract (sample), and b is the initial velocity of the reaction with extract but without enzyme (sample blank). The α-glucosidase inhibitory activity was determined using Saccharomyces cerevisiae α-glucosidase (type 1, ≥10 U/mg protein, 100 μL of 0.1 U/mL) as an enzyme, p-nitrophenylα-D-glucopyranoside (50 μL of 2 mM) as a substrate and an indicator, and a plant extract (50 μL) as an inhibitor as previously described [56]. The inhibitory activity was monitored at 405 nm using the microplate reader, and the results were expressed as the inhibition percentage as above.…”
Section: Enzyme Inhibitory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation